Perlindungan Hukum Bagi IDPs (Internally Displaced Persons) di Suriah dalam Perspektif Hukum Pengungsi Internasional - Tania Valeria Leimena; Josina Augustina Yvonne Wattimena; Richard Marsilio Waas (Faculty of Law, Universitas Pattimura, 2021)
Introduction: Declaration of Human Rights and Guiding on Internal Displacement which are the rights that have been regulated for IDPs (Internally Displaced Persons) in Syria.Purposes of the Research: The purpose of this article is to find out about the arrangements and forms of legal protection for IDPs (Internally Displaced Persons), especially women and children who experience sexual abused in Syrian conflict.Methods of the Research: The type of research used is normative juridical research or literature law research with descriptive-analytical documents obtained by normative juridical research then analyzed and conclusions drawn, and uses three approaches including the statutory approaches, case approaches, and conseptual approaches.Results of the Research: The results showed that Regulations regarding IDPs in the perspective of International Refugee Law have been regulated, the UN has established an arrangement, namely the Guiding Principles on Internal Displacement, however, this principle is soft law. Over time, the ICGLR established special protocols for IDPs such as The Protocol on the Protection and Assistance to Internally Displaced Persons, The Protocol on the Property Rights of Returning Person, and the Protocol on the Prevention and Suppression of Sexual Violence Against Women and Children. Forms of legal protection for IDPs in Syria in the perspective of International Refugee Law, namely the Legal Position in regulating internal refugees, and fulfilling the rights and obligations of Syrian refugees required in handling refugees by implementing the rules in regulated principles and protocols Given that until now, protection for IDPs has not been handled properly in terms of assistance services, health, education, legal protection, placement and provision of decent work.